The Regional Western Sweden SOM Survey 2012 - SOM Institute, University of Gothenburg (University of Gothenburg, 2014)
Western SOM has been conducted yearly since 1992, but was initially limited to residents of Gothenburg and its surrounding municipalities. In 1998, the survey was extended to include the entire Västra Götaland County plus the municipality of Kungsbacka.

The purpose of the regional surveys is to enable SOM researchers to study attitudes and behaviour linked to local and regional issues. They emphasise public services and media, although many of the questions are identical with those used in National SOM in order to make the answers comparable both between the regions and with Sweden at large.

Purpose:

Study attitudes and behaviors that are linked to local and regional issues and phenomena.

Väst-SOM har genomförts varje höst sedan 1992. Fram till 1997 omfattade studien Göteborg med kranskommuner, undersökningen utökades sedan till att omfatta hela Västra Götalands län samt Kungsbacka kommun.

Undersökningen syftar till att studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser. Tonvikten ligger på offentlig service och medier. Många av frågorna är identiska med frågor i Riks-SOM och Syd-SOM. Dessa studier är därmed jämförbara med varandra, både mellan de bägge regionerna och med Sverige som helhet.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser.
Den västsvenska SOM-undersökningen 2012
Väst-SOM 2012
Keywords: culture; kultur; trust; förtroende; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; information and communications technology; informations- och kommunikationsteknologi; newspaper readership; tidnings läsekrets; public transport; kollektivtrafik; radio; radio; medical care; sjukvård; radio news; radionyheter; television channels; tv-kanaler; news; nyheter; television news; tv-nyheter; political participation; politiskt deltagande; government; regering; internet; internet; information retrieval; informationssökning; democracy; demokrati; internal politics; inrikespolitik; leisure time activities; fritidsaktiviteter; commuting; pendling; refugees; flyktingar; personal safety; personlig trygghet; reading (activity); läsande; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap